A robust, distributed, and privacy-preserving aggregation scheme for smart grid communications. (2nd January 2019) - Shen, Gang; Su, Yixin; Zhang, Danhong; Zhang, Cheng; Zhang, Mingwu
ABSTRACT: Smart grid is a new type of power grid that integrates advanced information communication technology and measurement technology into conventional power grids. It provides an efficient and intelligent energy service. However, the entities in the smart grid are easily hacked and sometimes even collapsed; then the whole grid system could be jeopardized. Therefore, the security of user privacy and communication in smart grids is still facing great challenges. In this paper, we propose a robust, distributed, and privacy-preserving aggregation scheme, RDPA for short, which uses the homomorphic Paillier cryptosystem technique combined with signature technique to ensure the confidentiality and integrality of users' electricity consumption. In addition, we employ the threshold secret sharing technology and secret factors injection method to improve the robustness of smart grid systems. For example, RDPA can still run well even when a gateway is hacked. The experimental results and analysis demonstrate that RDPA can resist various attacks and protect user privacy, and its security and performance are better than other related schemes.